Lithium metal negative plate, lithium metal battery and preparation method of lithium metal negative plate
By using a composite layer on the negative electrode sheet of the lithium metal battery, including sulfur-containing compounds, fluorocarbon compounds and S-F bond-containing hydrocarbon derivatives, the safety and stability problems caused by the accumulation of dead lithium during the circulation of lithium metal batteries are solved, and higher cycle stability and electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411918338.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
AI Technical Summary
During the circulation process, lithium metal batteries are prone to puncture, short circuit and explosion of the diaphragm due to the aggregation and tip effect of dead lithium during the cycle, affecting the safety and stability of the battery.
A lithium metal negative electrode sheet is used, which includes a lithium metal layer and a composite layer. The composite layer is composed of sulfur-containing compounds, fluorocarbon compounds and S-F bond-containing hydrocarbon derivatives. The composite material is prepared by solvothermal reaction, mixed with a binder and a conductive agent, coated on the carrier film, and after drying and rolling, a lithium metal negative electrode sheet is formed.
Through the synergistic effect of S-F bonds and C-F bonds in the composite layer, the chemical stability and thermal stability of the electrode surface are improved, the migration and movement mechanics and electrochemical properties of Li+ are enhanced, the risk of dendrites of dead lithium to blocks is reduced, and the cycle stability and safety of lithium metal batteries are improved.
Smart Images

Figure CN119764342A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a lithium metal negative electrode sheet and a lithium metal battery and a method for preparing the same. Background Art
[0002] As a device that can convert energy between electrical energy and chemical energy, batteries are one of the best means of achieving electrical energy storage. In the past decade, the rapid development of commercial lithium-ion batteries has led to the booming consumer portable electronics and automotive industries such as electric vehicles. It is also because of the rapid innovation of these industries that new requirements have been put forward for lithium batteries with fast charging speed, long battery life, and greater safety and stability.
[0003] Theoretically, metallic lithium is the negative electrode material of lithium batteries with the highest specific capacity (3860mAh / g), and it also has the advantages of being the lightest and having the lowest potential, and is considered the ultimate choice for negative electrode material systems of lithium batteries. However, during the cycle of lithium metal batteries, dead lithium is deposited on the negative electrode surface every time it is charged and discharged. Most of these dead lithium are dendritic lithium, and their aggregation has a "tip effect", which makes it easier to puncture the diaphragm, causing the battery to short-circuit or even fail and cause an explosion. Solving its safety and stability problems has become a key technical challenge in the development of lithium metal batteries. Summary of the invention
[0004] In view of this, the present invention provides a lithium metal negative electrode sheet and a lithium metal battery and a preparation method thereof. The lithium metal negative electrode sheet and the lithium metal battery can solve the problems of safety and stability.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a lithium metal negative electrode sheet, which includes a lithium metal layer 10 and a composite layer 20, wherein the composite layer 20 is arranged on at least one surface of the lithium metal layer 10; the composite layer 20 includes a composite material, and the composite material includes a sulfur-containing compound, a fluorine-containing hydrocarbon compound and a hydrocarbon derivative containing an SF bond.
[0007] In an embodiment of the present invention, the sulfur-containing compound includes at least one of thiourea, thiamine, and zinc sulfide.
[0008] In an embodiment of the present invention, the fluorine-containing hydrocarbon compound includes at least one of geminal difluoroolefins, monofluoroolefins, trifluoroolefins, perfluoro compounds, and polytetrafluoroethylene.
[0009] In an embodiment of the present invention, the hydrocarbon derivative containing SF bond is obtained by reacting a sulfur-containing compound with a fluorine-containing hydrocarbon compound.
[0010] In an embodiment of the present invention, the lithium metal layer includes one of a copper-lithium composite strip, a lithium-aluminum alloy composite strip, a lithium-magnesium alloy composite strip, and a lithium-tin alloy composite strip.
[0011] Preferably, the single-side thickness of the composite layer is 5 to 20 μm.
[0012] Preferably, the thickness of the lithium metal layer is 20 to 50 μm.
[0013] In an embodiment of the present invention, the composite layer further includes a binder and a conductive agent.
[0014] In an embodiment of the present invention, the binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose.
[0015] In an embodiment of the present invention, the conductive agent includes at least one of conductive carbon black, acetylene black, graphene, conductive graphite, conductive carbon tube, and conductive carbon fiber.
[0016] Preferably, the mass ratio of the composite material, the binder and the conductive agent is (9-9.8):(0.4-0.8):(0.2-0.5).
[0017] In a second aspect, the present invention provides a method for preparing a lithium metal negative electrode sheet, comprising the following steps:
[0018] S1, mixing a sulfur-containing compound, a fluorine-containing hydrocarbon compound and a first solvent, and performing a solvothermal reaction to obtain a composite material;
[0019] S2, mixing the composite material, the binder, the conductive agent and the second solvent to prepare a slurry, coating the slurry on a carrier film, and obtaining a carrier film coated with a composite layer after drying;
[0020] S3, compounding the carrier film coated with the composite layer and the lithium metal layer, and removing the carrier film after rolling, to obtain a lithium metal negative electrode sheet.
[0021] Preferably, in step S1, the molar ratio of the sulfur-containing compound to the fluorine-containing hydrocarbon compound is (0.1-1):(0.1-1).
[0022] In an embodiment of the present invention, the first solvent includes at least one of benzene, toluene, xylene, and styrene.
[0023] Preferably, the temperature of the solvothermal reaction is 100 to 150° C., and the time of the solvothermal reaction is 8 to 15 hours.
[0024] In an embodiment of the present invention, in step S2, the second solvent includes at least one of N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylformamide.
[0025] In an embodiment of the present invention, the carrier film is a PET release film.
[0026] Preferably, the drying temperature is 60-100° C., and the drying time is 8-12 hours.
[0027] In a third aspect, the present invention provides a lithium metal battery, which includes the above-mentioned lithium metal negative electrode sheet, and / or the lithium metal negative electrode sheet prepared by the above-mentioned preparation method; the surface of the lithium metal negative electrode sheet includes block-shaped dead lithium.
[0028] In a fourth aspect, the present invention provides a method for preparing the above-mentioned lithium metal battery, comprising: assembling a lithium metal battery using a lithium metal negative electrode sheet, and applying pressure during the cycle of the lithium metal battery.
[0029] Preferably, the applied pressure is 0.4-1.2 MPa.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The lithium metal negative electrode sheet of the lithium metal battery of the present invention comprises a negative electrode current collector, a lithium metal layer and a composite layer, wherein the composite material in the composite layer comprises a sulfur-containing compound, a fluorine-containing hydrocarbon compound and a hydrocarbon derivative containing an SF bond.
[0032] Among them, fluorinated hydrocarbon compounds have CF bonds, which can improve the chemical and thermal stability of the electrode surface;
[0033] The high electronegativity of F element and Li + Affinity can show the maximum charge polarization, accelerating Li + Surface diffusion and enhanced Li + The migration kinetics of the electrodes improves the chemical and thermal stability of the electrode surface.
[0034] The S element in the composite material increases the Li + The transmission dynamics of
[0035] The SF bond of hydrocarbon derivatives has higher chemical energy and chemical stability, and can promote chemical reactions. It can enhance the reaction kinetics between the electrolyte and lithium metal, enhance the reaction activity of lithium metal batteries, and improve the electrochemical performance of lithium metal batteries.
[0036] 2. After applying appropriate pressure during the cycle of the lithium metal battery, the dead lithium in the battery will be transformed from dendrites to blocks, which greatly reduces the risk of puncturing the diaphragm and greatly improves the cycle stability of the lithium metal battery.
[0037] During the cycle of lithium metal batteries, applying pressure to lithium metal batteries will inevitably produce dendritic lithium, and the volume of dendritic lithium changes greatly, and the gradually thickening dead lithium layer will also cause the pressure between the positive and negative electrodes to become increasingly greater. Each deposition / stripping is like compressing the dead lithium layer again and again, which makes the dead lithium layer more and more dense, and the ion transmission channel becomes longer and more tortuous. The composite layer of the present invention can well improve this situation. The S element in the composite material of the composite layer of the present invention can form Li2S with Li, and Li2S has a very low Li diffusion energy (0.28V) and high ionic conductivity; the composite material reacts with Li to generate Li2O, and the lithium ions in Li2S react chemically with the oxygen generated by the electrolyte during the formation of the SEI film to generate Li2O, and Li2O has excellent lithium affinity and good crystal plane matching with lithium.
[0038] Therefore, the present invention can improve the length of the ion transmission channel caused by the increase in pressure in the later stage of the battery cycle through the synergistic effect of the S element and the CF bond, thereby improving the cycle stability of the lithium metal battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Shows the principle of SF bond formation.
[0040] Figure 2 It is a schematic diagram of the structure of the lithium metal negative electrode sheet of the present invention.
[0041] The reference numerals are as follows:
[0042] 10: Copper-lithium composite belt (lithium metal layer);
[0043] 11: Copper foil;
[0044] 12: lithium foil;
[0045] 20: Composite layer. DETAILED DESCRIPTION
[0046] The present invention discloses a lithium metal negative electrode sheet and a lithium metal battery and a method for preparing the same. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the same. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0047] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0048] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0049] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0050] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0051] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0052] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0053] Specifically, the present invention adopts the following technical solutions:
[0054] In a first aspect, the present invention provides a lithium metal negative electrode sheet, which includes a lithium metal layer 10 and a composite layer 20, wherein the composite layer 20 is arranged on at least one surface of the lithium metal layer 10; the composite layer 20 includes a composite material, and the composite material includes a sulfur-containing compound, a fluorine-containing hydrocarbon compound and a hydrocarbon derivative containing an SF bond.
[0055] In an embodiment of the present invention, the sulfur-containing compound includes but is not limited to at least one of thiourea, thiamine, and zinc sulfide.
[0056] In the embodiment of the present invention, the fluorine-containing hydrocarbon compound includes but is not limited to at least one of geminal difluoroolefins, monofluoroolefins, trifluoroolefins, perfluoro compounds, and polytetrafluoroethylene. The fluorine-containing hydrocarbon compound has a CF bond, which can improve the chemical stability and thermal stability of the electrode surface.
[0057] In an embodiment of the present invention, the geminal difluoroolefin includes at least one of 1,1-difluoro-2,2-diphenylethylene, 1,1-difluoro-2,2-di-4'-chlorophenylethylene, 1,1-difluoro-2,2-di-4'-fluorophenylethylene, and 1,1-difluoro-2-biphenylethylene.
[0058] In the embodiment of the present invention, the monofluoroolefin includes, for example, vinyl fluoride and the like.
[0059] In an embodiment of the present invention, the trifluoroolefin includes, for example, trifluoroethylene, trifluorochloroethylene, trifluorobromoethylene, cis-1-chloro-3,3,3-trifluoropropene, and the like.
[0060] In an embodiment of the present invention, the perfluorinated compound includes at least one of perfluoroethane, perfluoropropane, perfluorobutane, perfluoropentane, perfluorocyclopentane, and perfluorohexanone.
[0061] In an embodiment of the present invention, a hydrocarbon derivative containing an SF bond is obtained by reacting a sulfur-containing compound with a fluorine-containing hydrocarbon compound. The SF bond of the hydrocarbon derivative of the present invention has higher chemical energy and chemical stability, has a promoting effect on chemical reactions, can improve the reaction kinetics between the electrolyte and lithium metal, improve the reaction activity of the lithium metal battery, and improve the electrochemical performance of the lithium metal battery.
[0062] The fluorine-containing hydrocarbon compound and the hydrocarbon derivative containing the SF bond in the composite material of the present invention both contain the F element, and the high electronegativity of the F element and the Li + Affinity can show the maximum charge polarization, accelerating Li + Surface diffusion and enhanced Li + The migration kinetics of the electrodes are improved, which improves the chemical and thermal stability of the electrode surface.
[0063] The sulfur-containing compound and the hydrocarbon derivative containing SF bond in the composite material of the present invention both contain S element, which increases the Li + transmission dynamics.
[0064] In an embodiment of the present invention, the lithium metal layer includes but is not limited to one of a copper-lithium composite belt, a lithium-aluminum alloy composite belt, a lithium-magnesium alloy composite belt, and a lithium-tin alloy composite belt. Figure 2 As shown, when the lithium metal layer 10 is a copper-lithium composite tape, the copper-lithium composite tape includes a copper foil 11 and a lithium foil 12 .
[0065] Preferably, the thickness of the composite layer on one side is 5 to 20 μm. Exemplarily, the thickness of the composite layer on one side is any value among 5 μm, 7 μm, 9 μm, 10 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 20 μm or any value within the range of any two of the above values. When the thickness of the composite layer on one side is within this range, the chemical stability and thermal stability of the electrode surface can be improved, the reaction kinetics between the electrolyte and lithium metal can be enhanced, and the Li + The transport kinetics of lithium metal batteries can be further improved.
[0066] Preferably, the thickness of the lithium metal layer is 20 to 50 μm. Exemplarily, the thickness of the lithium metal layer is any value among 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or any value within the range of values formed by any two of the above values. If the thickness of the lithium metal layer is too thin, the pre-lithium amount will be insufficient, affecting the initial effect of the battery; if the thickness of the lithium metal layer is too thick, it will affect the volume energy density of the entire battery, and the lithium metal will easily denature and extend in the subsequent battery manufacturing process, causing a short circuit.
[0067] In an embodiment of the present invention, the composite layer further includes a binder and a conductive agent.
[0068] In an embodiment of the present invention, the binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and sodium carboxymethyl cellulose (CMC-Na).
[0069] In an embodiment of the present invention, the conductive agent includes but is not limited to at least one of conductive carbon black, graphene, conductive graphite, conductive carbon tubes, and conductive carbon fibers.
[0070] Preferably, the mass ratio of the composite material, the binder and the conductive agent is (9-9.8):(0.4-0.8):(0.2-0.5). Exemplarily, the mass ratio of the composite material, the binder and the conductive agent is any value in 9.5:0.1:0.4, 9:0.8:0.5, 9.8:0.4:0.2, 9:0.5:0.5, 9.2:0.4:0.4 or any value in the range of any two of the above values.
[0071] In a second aspect, the present invention provides a method for preparing a lithium metal negative electrode sheet, comprising the following steps:
[0072] S1, mixing a sulfur-containing compound, a fluorine-containing hydrocarbon compound and a first solvent, and performing a solvothermal reaction to obtain a composite material;
[0073] S2, mixing the composite material, the binder, the conductive agent and the second solvent to prepare a slurry, coating the slurry on a carrier film, and obtaining a carrier film coated with a composite layer after drying;
[0074] S3, compounding the carrier film coated with the composite layer and the lithium metal layer, and removing the carrier film after rolling, to obtain a lithium metal negative electrode sheet.
[0075] Preferably, in step S1, the molar ratio of the sulfur-containing compound to the fluorine-containing hydrocarbon compound is (0.1-1):(0.1-1). Exemplarily, the molar ratio of the sulfur-containing compound to the fluorine-containing hydrocarbon compound is any value among 0.1:1, 0.2:1, 0.4:1, 0.6:1, 0.8:1, 1:1, 1:0.8, 1:0.6, 1:0.4, 1:0.2, 1:0.1, or any value within the range consisting of any two of the above values.
[0076] In an embodiment of the present invention, the first solvent includes but is not limited to at least one of benzene, toluene, xylene, and styrene.
[0077] In an embodiment of the present invention, the ratio of the sulfur-containing compound to the first solvent is 1:(500-1000) in mmol / mL. Exemplarily, the ratio of the sulfur-containing compound to the first solvent is any value of 1:500, 1:600, 1:700, 1:800, 1:900, 1:1000 or any value within the range of any two of the above values.
[0078] Preferably, the temperature of the solvent thermal reaction is 100-150°C, and the time of the solvent thermal reaction is 8-15h. Exemplarily, the temperature of the solvent thermal reaction is any value in 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, or any value in the range of any two of the above values, and the time of the solvent thermal reaction is any value in 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, or any value in the range of any two of the above values. Within the temperature and time range of the above solvent thermal reaction, some sulfur-containing compounds and some fluorine-containing hydrocarbon compounds can react to generate hydrocarbon derivatives containing SF bonds, and the SF bonds contained therein have higher chemical energy and chemical stability, which have a promoting effect on chemical reactions, can improve the reaction kinetics between the electrolyte and lithium metal, improve the reaction activity of lithium metal batteries, and improve the electrochemical performance of lithium metal batteries.
[0079] In the embodiment of the present invention, the solvothermal reaction causes a portion of the S element in the sulfur-containing compound to undergo an ortho-cross reaction with the CF bond, and the S element replaces the C of the CF bond to form an SF bond. The SF bond has higher chemical energy and chemical stability, and has a promoting effect on the chemical reaction, which can improve the reaction kinetics between the electrolyte and lithium metal, improve the reaction activity of the lithium metal battery, and improve the electrochemical performance of the lithium metal battery. Since the chemical energy of the SF bond is very high and it is not easy to form, the composite material finally formed is a mixture of sulfur-containing compounds, fluorine-containing hydrocarbon compounds, and a small amount of the reaction products of the two.
[0080] Exemplarily, the SF bond formation principle is as follows Figure 1 shown.
[0081] In an embodiment of the present invention, the solvothermal reaction in step S1 includes steps of washing and drying the solid product.
[0082] In an embodiment of the present invention, the cleaning in step S1 is performed by using ethanol and distilled water alternately for 5 to 10 times.
[0083] In the embodiment of the present invention, the drying temperature in step S1 is 60-100° C., and the drying time is 8-12 hours.
[0084] In an embodiment of the present invention, in step S2, the second solvent includes but is not limited to at least one of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), and N,N-dimethylformamide (DMF).
[0085] In an embodiment of the present invention, the carrier film is a PET release film.
[0086] Preferably, the drying temperature in step S2 is 60-100°C, and the drying time is 8-12h. Exemplarily, the drying temperature is any value among 60°C, 70°C, 80°C, 90°C, 100°C, or any value within the range of any two of the above values, and the drying time is any value among 8h, 9h, 10h, 11h, 12h, or any value within the range of any two of the above values.
[0087] In a third aspect, the present invention provides a lithium metal battery, which includes the above-mentioned lithium metal negative electrode sheet, and / or the lithium metal negative electrode sheet prepared by the above-mentioned preparation method; the surface of the lithium metal negative electrode sheet includes block-shaped dead lithium.
[0088] In a fourth aspect, the present invention provides a method for preparing the above-mentioned lithium metal battery, comprising: assembling a lithium metal negative electrode sheet to obtain a lithium metal battery, and applying pressure during the cycle of the lithium metal battery. After applying appropriate pressure during the cycle of the lithium metal battery, the dead lithium in the battery will be transformed from dendrites to blocks, greatly reducing the risk of puncturing the diaphragm and greatly improving the cycle stability of the lithium metal battery.
[0089] During the cycle of lithium metal batteries, applying pressure to lithium metal batteries will inevitably produce dendritic lithium, and the volume change of dendritic lithium is quite large, and the gradually thickening dead lithium layer will also cause the pressure between the positive and negative electrodes to become larger and larger. Each deposition / stripping is like compressing the dead lithium layer again and again, which makes the dead lithium layer more and more dense, and the ion transmission channel becomes longer and longer, and more and more tortuous. The composite layer of the present invention can well improve this situation. The S element in the composite material of the composite layer of the present invention can form Li2S with Li, and Li2S has a very low Li diffusion energy (0.28V) and high ionic conductivity; the composite material will react with Li to generate Li2O, and the lithium ions in Li2S will react chemically with the oxygen generated by the electrolyte in the process of forming the SEI film to generate Li2O, and Li2O has excellent lithium affinity and good crystal plane matching with lithium. Therefore, the present invention can improve the length of the ion transmission channel caused by the increase in pressure in the later stage of the cycle of the battery through the synergistic effect of the S element and the CF bond, thereby improving the cycle stability of the lithium metal battery.
[0090] Preferably, the magnitude of the applied pressure is 0.4-1.2 MPa. Exemplarily, the magnitude of the applied pressure is any value among 0.4 MPa, 0.6 MPa, 0.8 MPa, 1.0 MPa, 1.2 MPa, or any value within the range formed by any two of the above values.
[0091] In the embodiment of the present invention, the battery structure includes but is not limited to a card battery, a button battery, a soft pack battery, a cylindrical battery, and the like.
[0092] The present application has no particular restrictions on the positive electrode sheet, separator, and electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.
[0093] The reagents, instruments or materials used in the present invention can be obtained through commercial channels.
[0094] The present invention will be further described below in conjunction with embodiments:
[0095] Embodiment 1:
[0096] The preparation method of the composite lithium metal negative electrode of this embodiment is as follows:
[0097] (1) Preparation method of composite material: 0.04 mmol of thiourea and polytetrafluoroethylene were added to 30 mL of toluene (C6H6) and stirred for 30 min. After stirring, the mixed solution was placed in a reactor and reacted at 120°C for 10 h. After the reaction was completed, the supernatant was poured out, and the bottom layer of the reacted material was taken out, and washed alternately with ethanol and distilled water for 6 times. The washed slurry was dried at 80°C for 12 h to obtain a composite material;
[0098] (2) Take 10g of the composite material, mix it with PVDF and carbon black in a ratio of 9.5:0.1:0.4, add an appropriate amount of NMP and grind it. After grinding for 30 minutes, a slurry of the composite material is obtained, which is then scraped on a PET film with a coating thickness of 20 mm. The coated material is placed in an oven for drying at a drying temperature of 80°C for 12 hours;
[0099] (3) The dried coating material is pasted together with the copper-lithium composite tape. The thickness of the copper-lithium composite tape is 38 microns (the thickness of the copper foil is 8 μm, and the thickness of the lithium foil is 30 μm). The coating is 20 mm, and the PET film is 8 mm, for a total of 66 mm. Except for the coating, the thickness of other materials does not change during rolling. The roller gap is set to 56 mm, and the coating is transferred to the surface of the copper-lithium composite tape under pressure. The transfer thickness is 10 mm. The composite lithium metal negative electrode sheet obtained by the transfer is combined with NCM613 to form a card battery. Figure 2 Schematic diagram of the structure of the lithium metal negative electrode sheet.
[0100] (4) The effective area of the cells that make up the card battery is 20cm 2 , put four card batteries into the three-layer pressure fixture, cover with the upper steel plate, connect the pressure sensor to the digital collector, tighten them diagonally in sequence until the pressure sensor displays a pressure of 0.6Mpa, and then test the electrochemical performance of the battery.
[0101] Embodiment 2:
[0102] The only difference between this embodiment and embodiment 1 is that the pressure displayed by the pressure sensor in step (4) is different, namely, 0.4 MPa.
[0103] The preparation method of the composite lithium metal negative electrode of this embodiment is as follows:
[0104] (1) Preparation method of composite materials: 0.04 mmol of thiourea and polytetrafluoroethylene were added to 30 mL of C6H6 and stirred for 30 min. After stirring, the mixed solution was placed in a reactor and reacted at 120°C for 10 h. After the reaction was completed, the supernatant was poured out, and the bottom layer of the reacted material was taken out, and washed alternately with ethanol and distilled water for 6 times. The washed slurry was dried at 80°C for 12 h to obtain a composite material;
[0105] (2) Take 10g of the composite material, mix it with PVDF and carbon black in a ratio of 9.5:0.1:0.4, add an appropriate amount of NMP and grind it. After grinding for 30 minutes, a slurry of the composite material is obtained, which is then scraped on a PET film with a coating thickness of 20 mm. The coated material is placed in an oven for drying at a drying temperature of 80°C for 12 hours;
[0106] (3) The dried coating material is pasted together with the copper-lithium composite tape. The thickness of the copper-lithium composite tape is 38 microns, plus the coating is 20 mm, and the PET film is 8 mm, for a total of 66 mm. Except for the coating, the thickness of other materials does not change during rolling. The roller gap is set to 56 mm, and the coating is transferred to the surface of the copper-lithium composite tape under pressure. The transfer thickness is 10 mm. The composite lithium metal negative electrode sheet obtained by transfer is combined with NCM613 to form a card battery.
[0107] (4) The effective area of the cells that make up the card battery is 20cm 2 , put four card batteries into the three-layer pressure fixture, cover with the upper steel plate, connect the pressure sensor to the digital collector, tighten them diagonally in sequence until the pressure sensor displays a pressure of 0.4Mpa, and then test the electrochemical performance of the battery.
[0108] Embodiment 3:
[0109] The only difference between this embodiment and embodiment 1 is that the pressure displayed by the pressure sensor in step (4) is different, namely, 0.9 MPa.
[0110] The preparation method of the composite lithium metal negative electrode of this embodiment is as follows:
[0111] (1) Preparation method of composite materials: 0.04 mmol of thiourea and polytetrafluoroethylene were added to 30 mL of C6H6 and stirred for 30 min. After stirring, the mixed solution was placed in a reactor and reacted at 120°C for 10 h. After the reaction was completed, the supernatant was poured out, and the bottom layer of the reacted material was taken out, and washed alternately with ethanol and distilled water for 6 times. The washed slurry was dried at 80°C for 12 h to obtain a composite material;
[0112] (2) Take 10g of the composite material, mix it with PVDF and carbon black in a ratio of 9.5:0.1:0.4, add an appropriate amount of NMP and grind it. After grinding for 30 minutes, a slurry of the composite material is obtained, which is then scraped on a PET film with a coating thickness of 20 mm. The coated material is placed in an oven for drying at a drying temperature of 80°C for 12 hours;
[0113] (3) The dried coating material is pasted together with the copper-lithium composite tape. The thickness of the copper-lithium composite tape is 38 microns, plus the coating is 20 mm, and the PET film is 8 mm, for a total of 66 mm. Except for the coating, the thickness of other materials does not change during rolling. The roller gap is set to 56 mm, and the coating is transferred to the surface of the copper-lithium composite tape under pressure. The transfer thickness is 10 mm. The composite lithium metal negative electrode sheet obtained by transfer is combined with NCM613 to form a card battery.
[0114] (4) The effective area of the cells that make up the card battery is 20cm 2 , put four card batteries into the three-layer pressure fixture, cover with the upper steel plate, connect the pressure sensor to the digital collector, tighten them diagonally in sequence until the pressure sensor displays a pressure of 0.9Mpa, and then test the battery's electrochemical performance.
[0115] Embodiment 4:
[0116] The only difference between this embodiment and embodiment 1 is that the pressure displayed by the pressure sensor in step (4) is different, namely, 1.2 MPa.
[0117] The preparation method of the composite lithium metal negative electrode of this embodiment is as follows:
[0118] (1) Preparation method of composite materials: 0.04 mmol of thiourea and polytetrafluoroethylene were added to 30 mL of C6H6 and stirred for 30 min. After stirring, the mixed solution was placed in a reactor and reacted at 120°C for 10 h. After the reaction was completed, the supernatant was poured out, and the bottom layer of the reacted material was taken out, and washed alternately with ethanol and distilled water for 6 times. The washed slurry was dried at 80°C for 12 h to obtain a composite material;
[0119] (2) Take 10g of the composite material, mix it with PVDF and carbon black in a ratio of 9.5:0.1:0.4, add an appropriate amount of NMP and grind it. After grinding for 30 minutes, a slurry of the composite material is obtained, which is then scraped on a PET film with a coating thickness of 20 mm. The coated material is placed in an oven for drying at a drying temperature of 80°C for 12 hours;
[0120] (3) The dried coating material is pasted together with the copper-lithium composite tape. The thickness of the copper-lithium composite tape is 38 microns, plus the coating is 20 mm, and the PET film is 8 mm, for a total of 66 mm. Except for the coating, the thickness of other materials does not change during rolling. The roller gap is set to 56 mm, and the coating is transferred to the surface of the copper-lithium composite tape under pressure. The transfer thickness is 10 mm. The composite lithium metal negative electrode sheet obtained by transfer is combined with NCM613 to form a card battery.
[0121] (4) The effective area of the cells that make up the card battery is 20cm2 , put four card batteries into the three-layer pressure fixture, cover with the upper steel plate, connect the pressure sensor to the digital collector, tighten them diagonally in sequence until the pressure sensor displays a pressure of 1.2Mpa, and then test the battery's electrochemical performance.
[0122] Embodiment 5:
[0123] The only difference between this embodiment and embodiment 1 is that the pressure process in step (4) is not performed.
[0124] The preparation method of the composite lithium metal negative electrode of this embodiment is as follows:
[0125] (1) Preparation method of composite materials: 0.04 mmol of thiourea and polytetrafluoroethylene were added to 30 mL of C6H6 and stirred for 30 min. After stirring, the mixed solution was placed in a reactor and reacted at 120°C for 10 h. After the reaction was completed, the supernatant was poured out, and the bottom layer of the reacted material was taken out, and washed alternately with ethanol and distilled water for 6 times. The washed slurry was dried at 80°C for 12 h to obtain a composite material;
[0126] (2) Take 10 g of the composite material, mix it with PVDF and carbon black in a ratio of 9.5:0.1:0.4, add an appropriate amount of NMP and grind it. After grinding for 30 minutes, a slurry of the composite material is obtained, which is scraped onto a PET film with a coating thickness of 20 mm. The coated material is placed in an oven for drying at a drying temperature of 80°C for 12 hours.
[0127] (3) The dried coating material is pasted together with the copper-lithium composite tape. The thickness of the copper-lithium composite tape is 38 μm, plus the coating is 20 mm, and the PET film is 8 mm, for a total of 66 mm. Except for the coating, the thickness of other materials does not change during rolling. The roller gap is set to 56 mm, and the coating is transferred to the surface of the copper-lithium composite tape under pressure. The transfer thickness is 10 mm. The composite lithium metal negative electrode sheet obtained by transfer is combined with NCM613 to form a card battery. Comparative Example 1:
[0128] The only difference between this comparative example and Example 1 is that no coating is added and no pressure process is performed.
[0129] The preparation method of the composite lithium metal negative electrode of this comparative example is as follows:
[0130] The unmodified copper-lithium composite tape has a thickness of 38 μm and a size of 3.2 cm × 4.2 cm, and is combined with NCM613 to form a card battery.
[0131] Battery performance test:
[0132] (1) Gram capacity test: the test temperature is 25℃, the test voltage range is 2.8V~4.4V, 1) the battery is allowed to stand for 10min; 2) 0.1C constant current charge to 4.4V, then 4.4V constant voltage charge to current ≤0.05C; 3) the battery is allowed to stand for 5min; 4) 0.1C constant current discharge to 2.8V; 5) the battery is allowed to stand for 5min, and the discharge capacity of the first cycle of 0.1C is recorded as the gram capacity.
[0133] (2) Cycle performance test: The test temperature was 25°C and the test voltage range was 2.8-4.35V. The batteries prepared in the examples and comparative examples were connected to a charging cabinet and first charged to 4.35V with a constant current of 0.1C. After standing for 5 min, the batteries were discharged to 2.8V with a constant current of 0.1C and then stood for 5 min. The discharge capacity at this time was recorded as the initial battery capacity. This step was repeated twice and then stood for 30 min to complete the formation step; the batteries were charged to 4.35V with a constant current of 0.33C and then charged at a constant voltage to a current ≤0.05C. After standing for 5 minutes, the batteries were discharged to 2.8V with a constant current of 0.5C and then stood for 5 min. This step was repeated until the battery capacity was 80% of the initial battery capacity and the number of cycles was recorded.
[0134] Table 1 shows the gram capacity of the composite lithium metal negative electrode for NCM613 card battery and the battery cycle performance in the examples and comparative examples.
[0135] Table 1
[0136]
[0137]
[0138] It can be seen from the results in Table 1 that compared with the unmodified lithium metal battery in Comparative Example 1, the modified composite lithium metal batteries in Examples 1-3 have greatly improved cycle performance under pressure. Under the action of pressure in the later stage of battery cycle, the dead lithium in the battery is transformed from dendrite to block, which reduces the risk of puncturing the diaphragm, but also increases the Li + The difficulty of migration between the positive and negative electrodes, and the role of the composite layer happens to make up for this defect very well, which can not only reduce the generation of dendrite lithium under the action of pressure, but also increase the Li + The migration kinetics of lithium metal batteries are improved.
[0139] The cycle performance of Example 4 is improved compared with that of Comparative Example 1, but the greater pressure will cause the lithium blocks to be crushed, and dendrites are easily grown on the broken lithium blocks, so the performance is reduced compared with Examples 1-3.
[0140] The cycle performance of Example 5 is improved compared with that of Comparative Example 1, but the pressure process is not used, so the dead lithium in the battery cannot be transformed from dendrites to blocks, so the performance is reduced relative to Examples 1-3.
[0141] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A lithium metal negative electrode sheet, characterized in that: The lithium metal negative electrode sheet comprises a lithium metal layer (10) and a composite layer (20), wherein the composite layer (20) is arranged on at least one surface of the lithium metal layer (10); the composite layer (20) comprises a composite material, wherein the composite material comprises a sulfur-containing compound, a fluorine-containing hydrocarbon compound and a hydrocarbon derivative containing an SF bond.
2. The lithium metal negative electrode sheet according to claim 1, characterized in that: The sulfur-containing compound includes at least one of thiourea, thiamine, and zinc sulfide; And / or, the fluorine-containing hydrocarbon compound includes at least one of geminal difluoroolefins, monofluoroolefins, trifluoroolefins, perfluoro compounds, and polytetrafluoroethylene; And / or, the hydrocarbon derivative containing SF bond is obtained by reacting a sulfur-containing compound with a fluorine-containing hydrocarbon compound.
3. The lithium metal negative electrode sheet according to claim 1, characterized in that: The lithium metal layer includes one of a copper-lithium composite belt, a lithium-aluminum alloy composite belt, a lithium-magnesium alloy composite belt, and a lithium-tin alloy composite belt.
4. The lithium metal negative electrode sheet according to claim 1, characterized in that: The single-side thickness of the composite layer is 5 to 20 μm; And / or, the thickness of the lithium metal layer is 20-50 μm.
5. The lithium metal negative electrode sheet according to claim 1, characterized in that: The composite layer also includes a binder and a conductive agent; The binder includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, and sodium carboxymethyl cellulose; The conductive agent includes at least one of conductive carbon black, acetylene black, graphene, conductive graphite, conductive carbon tube, and conductive carbon fiber; The mass ratio of the composite material, the binder and the conductive agent is (9-9.8):(0.4-0.8):(0.2-0.5).
6. A method for preparing a lithium metal negative electrode sheet, characterized in that: The steps include: S1, mixing a sulfur-containing compound, a fluorine-containing hydrocarbon compound and a first solvent, and performing a solvothermal reaction to obtain a composite material; S2, mixing the composite material, the binder, the conductive agent and the second solvent to prepare a slurry, coating the slurry on a carrier film, and obtaining a carrier film coated with a composite layer after drying; S3, compounding the carrier film coated with the composite layer and the lithium metal layer, and removing the carrier film after rolling to obtain a lithium metal negative electrode sheet.
7. The preparation method according to claim 6, characterized in that: In step S1, the molar ratio of the sulfur-containing compound to the fluorine-containing hydrocarbon compound is (0.1-1):(0.1-1); and / or, the first solvent comprises at least one of benzene, toluene, xylene, and styrene; And / or, the temperature of the solvent thermal reaction is 100-150° C., and the time of the solvent thermal reaction is 8-15 hours.
8. The preparation method according to claim 6, characterized in that: In step S2, the second solvent includes at least one of N-methylpyrrolidone, dimethyl sulfoxide, and N,N-dimethylformamide; And / or, the carrier film is a PET release film; And / or, the drying temperature is 60-100° C., and the drying time is 8-12 hours.
9. A lithium metal battery, characterized in that: The lithium metal battery comprises the lithium metal negative electrode sheet as described in any one of claims 1 to 5, and / or the lithium metal negative electrode sheet prepared by the preparation method as described in any one of claims 6 to 8; the surface of the lithium metal negative electrode sheet comprises block-shaped dead lithium.
10. The method for preparing a lithium metal battery according to claim 9, characterized in that: include: Assembling a lithium metal battery using the lithium metal negative electrode sheet, and applying pressure during the cycle of the lithium metal battery; The magnitude of the applied pressure is 0.4-1.2Mpa.
Citation Information
Patent Citations
Preparation method of lithium ion battery anode material LixMoS2
CN102403499A
Lithium ion battery anode material and preparation method thereof
CN109768265A
Coated lithium electrodes
US20020182508A1